High-transparency high-barrier bio-based copolymer nylon composite material and preparation method thereof
By treating bio-based copoly nylon resin and nanocellulose in a screw extruder, bio-based copoly nylon composite materials with high transparency, high barrier properties and high solvent resistance are prepared, which solves the shortcomings of existing transparent nylon materials in terms of barrier properties and achieves widespread application in food packaging and other fields.
Patent Information
- Application Number
- CN202510054953.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing transparent nylon materials have insufficient performance in blocking polar solvents or water vapor, which limits their application in food packaging, medical devices and other fields.
Using bio-based copoly nylon composite material, materials with excellent transparency, barrier properties and solvent resistance are prepared by mixing and dispersing the bio-based copoly nylon resin with nanocellulose, compatible agents, antioxidants and additives, and melt extrusion, traction and granulation in a screw extruder.
It has achieved high transparency, high barrier properties and high solvent resistance, and the material has excellent heat resistance, mechanical properties and toughness, and is suitable for food packaging, medical devices and other fields.
Smart Images

Figure CN119842226A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon resin and composite materials thereof, and in particular to a highly transparent and high-barrier bio-based copolymer nylon composite material and a preparation method thereof. Background Art
[0002] Polyamide (PA), commonly known as nylon, is a widely used engineering plastic. Nylon has been widely used in the fields of automobiles, electronics, textiles, etc. due to its excellent mechanical properties, lubrication resistance, and easy modification production. At present, the products of petroleum-based nylon materials such as aromatic nylon 6 and nylon 66 and semi-aromatic nylon 46, nylon 6T, nylon 9T, etc., which are widely used in industry, are mainly made from the reprocessing of by-products of petroleum refining. They are highly dependent on petroleum, and there are environmental pollution problems in the preparation and processing. Therefore, bio-based nylon materials prepared using renewable biomass resources as raw materials have received widespread attention.
[0003] Bio-based nylon materials refer to the raw materials needed to produce nylon (generally dibasic acids, diamines or cyclic lactams) using renewable biomass resources (such as glucose, cellulose, vegetable oil, etc.) and prepared through bioengineering methods. Common bio-based nylon materials include nylon 56, nylon 510, nylon 5T, nylon 11, etc., which have many applications in food packaging, clothing fibers, natural gas pipelines, medical protective glasses, automotive oil pipelines, machinery and other fields.
[0004] Transparent nylon is a type of specialty nylon. It is widely used in food packaging, electronics, machinery, optics and other fields due to its high transparency, solvent resistance, low density, wear resistance and flexibility. However, traditional transparent nylon generally adopts an amorphous aggregate structure design, such as nylon TMDT and nylon CM12. This amorphous aggregate structure design achieves good transparency by destroying the regularity of the molecular chain. However, this amorphous aggregate structure design makes it difficult for transparent nylon to block the penetration of polar solvents or water vapor, and has problems with poor barrier properties and solvent resistance, which limits its application. For example, medical devices and food packaging that require high-temperature steam sterilization, smart wearable electronics and flexible displays that need to be frequently cleaned in contact with polar solvents. The Chinese patent technology with publication number CN 101768302 A discloses a method for preparing a high-barrier polyethylene / nylon 6 in-situ nanocomposite material, which uses a screw extruder to react and extrude polyethylene, caprolactam, intercalated montmorillonite, a compatibilizer, an anionic initiator and a co-catalyst to prepare a high-barrier polyethylene / nylon 6 in-situ nanocomposite material. However, the patent adds montmorillonite during the preparation process, and the addition of montmorillonite will cause the high-barrier polyethylene / nylon 6 in-situ nanocomposite material to have poor transparency, which limits its application in food packaging, medical devices, smart wearable electronics, flexible displays and other fields.
[0005] Therefore, how to obtain a bio-based nylon material that has excellent transparency, barrier properties and solvent resistance is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The invention provides a highly transparent and high-barrier bio-based copolymer nylon composite material, wherein the bio-based nylon composite material has excellent transparency, barrier and solvent resistance, and also has excellent heat resistance, mechanical properties and toughness.
[0007] The present invention also provides a method for preparing a highly transparent and high-barrier bio-based copolymer nylon composite material, by which a bio-based nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness can be prepared.
[0008] The first aspect of the present invention provides a highly transparent and high-barrier bio-based copolymer nylon composite material, wherein the raw materials for preparing the bio-based nylon composite material include a bio-based copolymer nylon resin, nanocellulose, a compatibilizer, an antioxidant, and a first auxiliary agent;
[0009] The bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510 or bio-based copolymer nylon resin 5T / 512.
[0010] The highly transparent and high-barrier bio-based copolymer nylon composite material as described above, in terms of weight parts, includes 92 to 98 parts of the bio-based copolymer nylon resin, 1 to 5 parts of the nanocellulose, 1 to 5 parts of the compatibilizer, 0.1 to 0.5 parts of the antioxidant, and 0.1 to 2 parts of the first auxiliary agent.
[0011] As for the highly transparent and high-barrier bio-based copolymer nylon composite material as described above, the relative viscosity of the bio-based copolymer nylon resin 5T / 510 is 2.42-2.56, and the relative viscosity of the bio-based copolymer nylon resin 5T / 512 is 2.61-2.63.
[0012] In the highly transparent and high-barrier bio-based copolymer nylon composite material as described above, the length of the nanocellulose is less than 300 nm.
[0013] In the highly transparent and high-barrier bio-based copolymer nylon composite material as described above, the carboxyl content in the nanocellulose is 1.2 mmol / g to 3.0 mmol / g.
[0014] The highly transparent and high-barrier bio-based copolymer nylon composite material as described above, wherein the compatibilizer is at least one of ethylene acrylate copolymer, ethylene-octene copolymer grafted with maleic anhydride, and glycidyl methacrylate grafted modified polyether block amide copolymer;
[0015] And / or, the antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 264, antioxidant TNP, and antioxidant TPP;
[0016] And / or, the first auxiliary agent includes a lubricant.
[0017] The highly transparent and high-barrier bio-based copolymer nylon composite material as described above, the preparation process of the bio-based copolymer nylon resin is as follows:
[0018] The dibasic acid, terephthalic acid and deionized water are mixed, and then 1,5-pentanediamine is added to carry out a neutralization reaction to obtain a mixed solution of nylon 5T salt;
[0019] The catalyst, the end-capping agent, the second auxiliary agent and the mixed solution of the nylon 5T salt are mixed and concentrated and prepolymerized to obtain a nylon 5T prepolymer;
[0020] The nylon 5T prepolymer is polymerized under vacuum negative pressure conditions to obtain a bio-based copolymer nylon resin.
[0021] The highly transparent and high-barrier bio-based copolymer nylon composite material as described above, wherein the dibasic acid is sebacic acid or dodecanedioic acid;
[0022] When the dibasic acid is sebacic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510;
[0023] When the diacid is dodecanedioic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 512.
[0024] The second aspect of the present invention provides a method for preparing the highly transparent and high-barrier bio-based copolymer nylon composite material, comprising:
[0025] Preparation of bio-based copolymer nylon resin;
[0026] Preparation of bio-based copolymer nylon composites:
[0027] The bio-based copolymer nylon resin, nanocellulose, compatibilizer, antioxidant and first auxiliary agent are mixed and dispersed to obtain a mixture, and then the mixture is melt-extruded, pulled and granulated in a screw extruder to obtain a bio-based copolymer nylon composite material.
[0028] In the method for preparing the highly transparent and high-barrier bio-based copolymer nylon composite material as described above, the temperature of the melt extrusion is 260°C to 280°C.
[0029] The highly transparent and high-barrier bio-based copolymer nylon composite material provided by the present invention is prepared from raw materials including bio-based copolymer nylon resin, nanocellulose, compatibilizer, antioxidant and first auxiliary agent. The light transmittance of the bio-based nylon composite material can reach 91.8%, and it can effectively block the penetration of oxygen, water vapor and polar solvent (N, N-dimethylformamide in the embodiment of the present invention), which shows that the bio-based nylon composite material has excellent transparency, barrier properties and solvent resistance, and it also has excellent heat resistance (glass transition temperature can reach 109 ° C), mechanical properties (tensile strength can reach 91MPa) and toughness (bending strength can reach 158MPa), and has broad application prospects in the fields of food packaging, medical devices, smart wearable electronics, flexible displays, etc. In addition, compared with traditional petroleum-based nylon materials, the bio-based copolymer nylon composite material is a bio-based nylon material with the advantage of environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1This is the infrared spectrum of PA5T / 510 in Example 1 of the present invention;
[0032] Figure 2 This is an infrared spectrum of the bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention;
[0033] Figure 3 The X-ray diffraction pattern of the PA5T / 510 and bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention;
[0034] Figure 4 This is a DSC thermal analysis test diagram of the PA5T / 510 and bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention;
[0035] Figure 5 The bio-based copolymer nylon composite material after soaking in Example 1 to Example 4 of the present invention;
[0036] Figure 6 The bio-based copolymer nylon composite material after soaking in Comparative Examples 1 to 4 of the present invention;
[0037] Figure 7 This is the bio-based copolymer nylon composite material after immersion in Comparative Examples 5 and 6 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials and reagents used in the following examples can be obtained from commercial sources; the processes used, unless otherwise specified, are conventional processes in the art.
[0040] It should be noted that the descriptions involving “first”, “second”, etc. in the present invention are used to distinguish similar objects, but are not used to describe a specific order or sequence, and therefore cannot be understood as a limitation of the present invention.
[0041] In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the previously and subsequently associated objects are in an "or" relationship.
[0042] The first aspect of the present invention provides a highly transparent and high-barrier bio-based copolymer nylon composite material, wherein the raw materials for preparing the bio-based nylon composite material include a bio-based copolymer nylon resin, nanocellulose, a compatibilizer, an antioxidant, and a first auxiliary agent;
[0043] The bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510 or bio-based copolymer nylon resin 5T / 512.
[0044] Specifically, the bio-based copolymer nylon composite material of the present invention can be prepared from raw materials including bio-based copolymer nylon resin 5T / 510, nanocellulose, a compatibilizer, an antioxidant and a first auxiliary agent, or can be prepared from raw materials including bio-based copolymer nylon resin 5T / 512, nanocellulose, a compatibilizer, an antioxidant and a first auxiliary agent. The bio-based copolymer nylon composite material has excellent transparency (light transmittance can reach 91.8%), barrier properties (can effectively block the penetration of oxygen and water vapor) and solvent resistance (can effectively block the penetration of polar solvents), and it also has excellent heat resistance (glass transition temperature can reach 109°C), mechanical properties (tensile strength can reach 91MPa) and toughness (bending strength can reach 158MPa). The inventors analyzed this and believed that the reasons may be: (1) the crystal form of bio-based copolymer nylon resin 5T / 510 or bio-based copolymer nylon resin 5T / 510 is similar to that of nanocellulose, which greatly reduces the interface reflection and diffraction phenomenon between nanocellulose and bio-based copolymer nylon resin 5T / 510 or bio-based copolymer nylon resin 5T / 510, making it easier for light to penetrate the material and achieve high transmittance. Therefore, the bio-based copolymer nylon composite material has excellent transparency; (2) the heterogeneous isomorphous co-crystal aggregation structure design is adopted, and the carbon chain is longer. Therefore, the prepared bio-based copolymer nylon composite material has the advantages of strong barrier properties, excellent solvent resistance, excellent heat resistance, excellent mechanical properties and excellent toughness.
[0045] The present invention does not particularly limit the sources of the raw materials used above, and they can be purchased through commercial channels or prepared by methods well known in the art.
[0046] In a specific embodiment, in the above-mentioned preparation raw materials, by weight, the bio-based copolymer nylon resin is 92 to 98 parts, the nanocellulose is 1 to 5 parts, the compatibilizer is 1 to 5 parts, the antioxidant is 0.1 to 0.5 parts, and the first auxiliary agent is 0.1 to 2 parts.
[0047] When the proportions of the bio-based copolymer nylon resin, nanocellulose, compatibilizer, antioxidant and the first auxiliary agent in the above-mentioned preparation raw materials are within the above-mentioned ranges, the bio-based copolymer nylon resin, nanocellulose, compatibilizer, antioxidant and the first auxiliary agent can have a good synergistic effect, thereby preparing a bio-based copolymer nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness.
[0048] In a specific embodiment, the relative viscosity of the bio-based copolymer nylon resin 5T / 510 is 2.42-2.56, and the relative viscosity of the bio-based copolymer nylon resin 5T / 512 is 2.61-2.63.
[0049] When the relative viscosity of the above-mentioned bio-based copolymer nylon resin 5T / 510 or the relative viscosity of the above-mentioned bio-based copolymer nylon resin 5T / 512 is within the above-mentioned range, a bio-based copolymer nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness can be prepared.
[0050] In a specific embodiment, the length of the nanocellulose is less than 300 nm, more preferably 200 nm to 300 nm.
[0051] In a specific embodiment, the carboxyl content in the nanocellulose is 1.2 mmol / g to 3.0 mmol / g.
[0052] When the length of nanocellulose and the carboxyl content in nanocellulose are within the above range, a bio-based copolymerized nylon composite material with high barrier properties and high transparency can be prepared. The inventors analyzed this and believed that the reasons may be: (1) the carboxyl groups in nanocellulose and the amide bonds in the bio-based copolymerized nylon resin undergo amide exchange to form a chemical graft, and due to the nanoscale effect of nanocellulose, the prepared bio-based copolymerized nylon composite material has high barrier properties to oxygen, water vapor and polar solvents; (2) the crystal form of the bio-based copolymerized nylon resin 5T / 510 or the bio-based copolymerized nylon resin 5T / 510 is similar to that of nanocellulose, which greatly reduces the interface reflection and diffraction phenomenon between nanocellulose and the bio-based copolymerized nylon resin 5T / 510 or the bio-based copolymerized nylon resin 5T / 510, making it easier for light to penetrate the material, so that the bio-based copolymerized nylon composite material has high transparency.
[0053] In a specific embodiment, the compatibilizer is at least one of ethylene acrylate copolymer, ethylene-octene copolymer grafted maleic anhydride, and methacrylate glycidyl grafted modified polyether block amide copolymer, preferably ethylene-octene copolymer grafted maleic anhydride (POE-g-MAH). The antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 264, antioxidant TNP, and antioxidant TPP. The first auxiliary agent includes a lubricant, and the lubricant is preferably bile wax.
[0054] When the above substances are selected as the compatibilizer, antioxidant and the first auxiliary agent respectively, the components in the preparation raw materials can be better matched, with better synergistic effects, which is beneficial to improving the overall performance of the above bio-based copolymer nylon composite material.
[0055] The present invention does not specifically limit the specific method for preparing the bio-based copolymer nylon resin, and the resin can be synthesized according to methods well known in the art or methods in the literature. In a specific embodiment, the preparation process of the bio-based copolymer nylon resin is as follows:
[0056] The dibasic acid, terephthalic acid and deionized water are mixed, and then 1,5-pentanediamine is added to carry out a neutralization reaction to obtain a mixed solution of nylon 5T salt;
[0057] The catalyst, the end-capping agent, the second auxiliary agent and the mixed solution of nylon 5T salt are mixed and concentrated and prepolymerized to obtain nylon 5T prepolymer;
[0058] The nylon 5T prepolymer is polymerized under vacuum negative pressure conditions to obtain a bio-based copolymer nylon resin.
[0059] The present invention can prepare bio-based copolymer nylon resin according to the above preparation method.
[0060] In one embodiment, the dibasic acid is sebacic acid or dodecanedioic acid;
[0061] When the dibasic acid is sebacic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510;
[0062] When the dibasic acid is dodecanedioic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 512.
[0063] When the above-mentioned dibasic acid is sebacic acid or dodecanedioic acid, a bio-based copolymer nylon resin 5T / 510 or a bio-based copolymer nylon resin 5T / 512 can be prepared, and thus a bio-based copolymer nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness can be prepared using the bio-based copolymer nylon resin 5T / 510 or the bio-based copolymer nylon resin 5T / 512.
[0064] In some embodiments, the total weight of the dibasic acid, terephthalic acid and 1,5-pentanediamine is 100 parts, the catalyst is 0.2 to 1 part, the end-capping agent is 0.1 to 0.5 parts, and the second auxiliary agent is 0.05 to 0.5 parts.
[0065] In some embodiments, the molar ratio of the dibasic acid, terephthalic acid and 1,5-pentanediamine is 4:1:5.
[0066] In some embodiments, the prepolymerization reaction is carried out at a temperature of 200° C. to 250° C., a pressure of 1.5 MPa to 1.7 MPa, and a time of 1 h to 2 h.
[0067] In some embodiments, the polymerization reaction temperature is 240° C. to 280° C., the reaction time is 1 h to 1.5 h, and the vacuum degree of the vacuum negative pressure is -0.05 Mpa to -0.08 Mpa.
[0068] In some embodiments, the catalyst is at least one of sodium hypophosphite, sodium phosphite, phosphate and hypophosphite, the end-capping agent is at least one of benzoic acid, terephthalic acid and 2-naphthalenecarboxylic acid, and the second auxiliary agent includes a metal salt, which may preferably be magnesium chloride.
[0069] The second aspect of the present invention provides a method for preparing a highly transparent and high-barrier bio-based copolymer nylon composite material, comprising:
[0070] Preparation of bio-based copolymer nylon resin;
[0071] Preparation of bio-based copolymer nylon composites:
[0072] The bio-based copolymer nylon resin, nanocellulose, a compatibilizer, an antioxidant and a first auxiliary agent are mixed and dispersed to obtain a mixture, and then the mixture is melt-extruded, pulled and granulated in a screw extruder to obtain a bio-based copolymer nylon composite material.
[0073] Specifically, the object prepared by the present invention is a bio-based copolymerized nylon composite material. First, the bio-based copolymerized nylon resin, nanocellulose, a compatibilizer, an antioxidant and a first auxiliary agent are mixed and dispersed to obtain a mixture. The mixing treatment is conducive to making various raw materials uniformly dispersed and interacting with each other, providing a stable material basis for subsequent processing steps such as melt extrusion, traction, and granulation; then the mixture is placed in a screw extruder, and the mixture is melt extruded, traction and granulated in the screw extruder to obtain a bio-based copolymerized nylon composite material with excellent transparency, barrier performance, solvent resistance, heat resistance, mechanical properties and toughness. The preparation method is simple in process and suitable for wide promotion and application.
[0074] In one specific embodiment, the temperature of melt extrusion is 260°C to 280°C.
[0075] When the parameters of the melt extrusion temperature are within the above range, the melt viscosity of the bio-based copolymer nylon resin can be effectively reduced, thereby improving its fluidity, helping to improve the dispersibility of nanocellulose in the bio-based copolymer nylon resin, allowing the nanocellulose and the bio-based copolymer nylon resin to undergo more complete amide exchange, forming more chemical grafting, and promoting the interface bonding between the nanocellulose and the bio-based copolymer nylon resin, thereby better exerting its reinforcing and modifying effects, thereby preparing a bio-based copolymer nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness.
[0076] For example, the melt extrusion temperature may be any one of 260° C., 265° C., 270° C., 275° C., or 280° C., or any two of these.
[0077] The present invention does not impose any particular limitation on the time of melt extrusion, which can be selected according to actual needs. In some embodiments, the residence time of melt extrusion is greater than 15 minutes.
[0078] The present invention describes the implementation mode of the present invention in detail through the following examples and comparative examples. The raw materials involved in the examples and comparative examples of the present invention are bio-based copolymerized nylon resin 5T / 510 (PA5T / 510), bio-based copolymerized nylon resin 5T / 512 (PA5T / 512), transparent nylon TR90 (purchased from EMS, Switzerland, molecular formula abbreviation PA MACM12), transparent nylon G21 (purchased from EMS, Switzerland, molecular formula abbreviation PA6I / 6T), nanocellulose A, nanocellulose B, nanocellulose C, nanocellulose D, ethylene-octene copolymer grafted maleic anhydride (POE-g-MAH), antioxidant 168, antioxidant 1010, and bile wax. The raw material formula is shown in Table 1 and Table 2:
[0079] Table 1 Raw material formula table of embodiment 1-embodiment 4 (by weight)
[0080] serial number Example 1 Example 2 Example 3 Example 4 PA5T / 510 92 92 0 0 PA5T / 512 0 0 92 92 PA MACM12 0 0 0 0 PA6I / 6T 0 0 0 0 Nanocellulose A 3 0 3 0 Nanocellulose B 0 3 0 3 Nanocellulose C 0 0 0 0 Nanocellulose D 0 0 0 0 POE-g-MAH 4 4 4 4 Antioxidant 168 0.2 0.2 0.2 0.2 Antioxidant 1010 0.2 0.2 0.2 0.2 Montan wax 0.6 0.6 0.6 0.2
[0081] Table 2 Raw material formula table of comparative example 1-comparative example 6 (by weight)
[0082]
[0083]
[0084] In Tables 1 and 2, nanocellulose (CNF) A is C916570-6% carboxylated cellulose nanofiber with a length of 200 nm and a carboxyl content of 2.1 mmol / g; nanocellulose (CNF) B is C916412-carboxylated cellulose nanofiber powder with a length of 200 nm and a carboxyl content of 2.1 mmol / g; nanocellulose (CNF) C is carboxyl-free nanocellulose with a length of 200 nm; nanocellulose (CNF) D is C916569-6% carboxylated nanocellulose with a length of 1000 nm and a carboxyl content of 2.1 mmol / g.
[0085] The bio-based copolymer nylon resin 5T / 510 used in the following embodiments of the present invention is prepared by the following process:
[0086] By weight, 55 parts of sebacic acid, 11 parts of terephthalic acid and 150 parts of deionized water were mixed to obtain a mixed solution, the mixed solution was stirred at a rotation speed of 120 rpm until the mixed solution was a white suspension, and then the white suspension was heated to 80° C., and 34 parts of 1,5-pentanediamine were added to carry out neutralization reaction for 1 hour to obtain a salt solution, and the pH value of the salt solution was adjusted to 7.5 to obtain a mixed solution of nylon 5T salt and nylon 510 salt;
[0087] 2 parts of sodium hypophosphite, 0.5 parts of benzoic acid, 0.5 parts of auxiliary magnesium chloride and 100 parts of a mixed solution of nylon 5T salt and nylon 510 salt are mixed to obtain a mixture; the mixture is added into an autoclave, the air in the autoclave is replaced with nitrogen for 5 times, and then the temperature is raised to 150° C., the pressure is kept stable at 1.5 MPa, and the mixture is concentrated to a water content of 20% to obtain a concentrated mixture; the temperature is further raised to 230° C., the pressure is kept stable at 1.6 MPa, and the concentrated mixture is prepolymerized for 1 hour to obtain a nylon 5T / 510 prepolymer;
[0088] The nylon 5T / 510 prepolymer was polymerized at a temperature of 260° C. for 1 hour under a vacuum negative pressure condition with a vacuum degree of -0.06 MPa to obtain a bio-based copolymer nylon resin 5T / 510 (PA5T / 510).
[0089] The bio-based copolymer nylon resin 5T / 512 used in the following embodiments of the present invention is prepared by the following process:
[0090] By weight, 58 parts of dodecanedioic acid, 10 parts of terephthalic acid and 155 parts of deionized water were mixed to obtain a mixed solution, the mixed solution was stirred at a rotation speed of 120 rpm until the mixed solution was a white suspension, and then the white suspension was heated to 80° C., and 32 parts of 1,5-pentanediamine were added to carry out neutralization reaction for 1 hour to obtain a salt solution, and the pH value of the salt solution was adjusted to 7.5 to obtain a mixed solution of nylon 5T salt and nylon 512 salt;
[0091] 2 parts of sodium hypophosphite, 0.5 parts of benzoic acid, 0.5 parts of magnesium chloride and 100 parts of a mixed solution of nylon 5T salt and nylon 512 salt are mixed to obtain a mixture; the mixture is added into an autoclave, the air in the autoclave is replaced with nitrogen for 5 times, and then the temperature is raised to 150° C., the pressure is kept stable at 1.5 MPa, and the mixture is concentrated to a water content of 20% to obtain a concentrated mixture; the temperature is further raised to 230° C., the pressure is kept stable at 1.6 MPa, and the concentrated mixture is prepolymerized for 1 hour to obtain a nylon 5T / 512 prepolymer;
[0092] The nylon 5T / 512 prepolymer was polymerized at a temperature of 260° C. for 1 hour under a vacuum negative pressure condition with a vacuum degree of -0.06 MPa to obtain a bio-based copolymer nylon resin 5T / 512 (PA5T / 512).
[0093] Example 1
[0094] In this embodiment, the bio-based copolymer nylon composite material is prepared by the following process:
[0095] Step S1: PA5T / 510, nanocellulose A, POE-g-MAH, antioxidant 168, antioxidant 1010 and montan wax are mixed and dispersed according to the raw material formula of Example 1 in Table 1 to obtain a mixture; then the mixture is placed in a screw extruder with a length-to-diameter ratio of 68:1, and the mixture is melt-extruded, pulled and granulated in the screw extruder to obtain a bio-based copolymer nylon composite material (PA5T / 510CNF), the temperature of the above-mentioned melt extrusion is 265°C, and the residence time of the above-mentioned melt extrusion is 15min.
[0096] Example 2
[0097] The preparation of the bio-based copolymer nylon composite material provided in this embodiment is basically the same as that in Example 1, except that:
[0098] The raw material formula is: 92 parts of PA5T / 510, 3 parts of nanocellulose B, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0099] Example 3
[0100] The preparation of the bio-based copolymer nylon composite material provided in this embodiment is basically the same as that in Example 1, except that:
[0101] The raw material formula is: 92 parts of PA5T / 512, 3 parts of nanocellulose A, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0102] Example 4
[0103] The preparation of the bio-based copolymer nylon composite material provided in this embodiment is basically the same as that in Example 1, except that:
[0104] The raw material formula is: 92 parts of PA5T / 512, 3 parts of nanocellulose B, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0105] Comparative Example 1
[0106] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0107] The raw material formula is: 92 parts of PA MACM12, 3 parts of nanocellulose A, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0108] Comparative Example 2
[0109] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0110] The raw material formula is: 92 parts of PA6I / 6T, 3 parts of nanocellulose A, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0111] Comparative Example 3
[0112] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0113] The raw material formula is: 92 parts of PA5T / 510, 3 parts of nanocellulose C, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0114] Comparative Example 4
[0115] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0116] The raw material formula is: 92 parts of PA5T / 510, 3 parts of nanocellulose D, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0117] Comparative Example 5
[0118] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0119] The temperature of melt extrusion was 220°C.
[0120] Comparative Example 6
[0121] The preparation of the bio-based copolymer nylon composite material provided in this comparative example is basically the same as that in Example 1, except that:
[0122] The raw material formula is: 95 parts of PA5T / 510, 4 parts of POE-g-MAH, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant 1010, and 0.6 parts of montan wax.
[0123] The temperature of melt extrusion was 220°C.
[0124] Performance Testing
[0125] 1. Infrared spectrum test
[0126] Figure 1 This is the infrared spectrum of PA5T / 510 in Example 1 of the present invention; Figure 2 This is the infrared spectrum of the bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention.
[0127] Depend on Figure 1 and Figure 2 It can be seen that compared with PA5T / 510, the stretching vibration peak (3280.15 cm -1 ) and CO stretching vibration peaks (at 1000-1350cm -1 There is no obvious abnormal peak or drastic change in the absorption peak in the infrared spectrum of the bio-based copolymer nylon composite material, which indicates that there is no obvious interaction between nanocellulose A and PA5T / 510 after adding nanocellulose A, indicating that nanocellulose A and PA5T / 510 have good compatibility.
[0128] 2. X-ray diffraction (XRD) test
[0129] Figure 3This is the X-ray diffraction pattern of the PA5T / 510 and bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention.
[0130] Depend on Figure 3 It can be seen that compared with PA5T / 510, the peak area in the spectrum of the bio-based copolymer nylon composite material (PA5T / 510CNF) increases, which indicates that its crystal content increases. It shows that the addition of nanocellulose A increases the content of the crystalline phase in the bio-based copolymer nylon composite material, improves the crystallinity of the bio-based copolymer nylon composite material, but does not change the crystal structure of PA5T / 510. The inventors analyzed this: this may be because the crystal form of nanocellulose A is similar to that of PA5T / 510, so the addition of nanocellulose A does not change the crystal structure of PA5T / 510.
[0131] 3.DSC thermal analysis test
[0132] Figure 4 This is a DSC thermal analysis test diagram of the PA5T / 510 and bio-based copolymer nylon composite material (PA5T / 510CNF) in Example 1 of the present invention.
[0133] Depend on Figure 4 It can be seen that compared with PA5T / 510, the melting peak area of the bio-based copolymer nylon composite material (PA5T / 510CNF) is larger, and the melting peak area is proportional to the melting enthalpy (ΔHm) of the material. This shows that the crystallinity of the bio-based copolymer nylon composite material (PA5T / 510CNF) after adding nanocellulose A increases, the crystallization process is more perfect, the proportion of the crystalline region in the bio-based copolymer nylon composite material (PA5T / 510CNF) increases, and a more ordered crystal structure is formed, which is beneficial to improve the thermal stability and mechanical properties of the material.
[0134] 4. Solvent resistance test
[0135] The solvent resistance test of the bio-based copolymer nylon composite materials of Examples 1 to 4 and Comparative Examples 1 to 6 was carried out respectively with reference to standard ISO 175. First, the mass of the bio-based copolymer nylon composite materials of each embodiment and each comparative example before immersion was measured, and then the bio-based copolymer nylon composite materials of each embodiment and each comparative example were bent and the bent part was completely immersed in N, N-dimethylformamide with a mass fraction of 99.8%. After immersion for 1 hour and drying, the mass of the bio-based copolymer nylon composite materials of each embodiment and each comparative example after immersion was measured, and the mass change rate (%) of the bio-based copolymer nylon composite materials of each embodiment and each comparative example before and after immersion was calculated. The results are shown in Table 3.
[0136] Table 3 Mass change rate of bio-based copolymer nylon composite materials before and after immersion in each embodiment and each comparative example
[0137] project Mass change rate, % Example 1 2.1 Example 2 1.8 Example 3 3.2 Example 4 2.5 Comparative Example 1 12.2 Comparative Example 2 16.8 Comparative Example 3 20.3 Comparative Example 4 11.1 Comparative Example 5 9.9 Comparative Example 6 13.1
[0138] From Table 3 and Figure 5-Figure 7 It can be seen that by comparing Examples 1 to 4 with Comparative Examples 1 to 6, it is found that the mass change rate of the bio-based copolymerized nylon composite materials prepared in Examples 1 to 4 is lower than the mass change rate of the bio-based copolymerized nylon composite materials prepared in Comparative Examples 1 to 6, which shows that the bio-based copolymerized nylon composite materials provided in the embodiments of the present invention can effectively block the penetration of polar solvents (N, N-dimethylformamide). Therefore, the bio-based copolymerized nylon composite materials provided in the embodiments of the present invention have excellent solvent resistance.
[0139] 5. Performance testing of bio-based copolymer nylon composites
[0140] The following tests were performed on the bio-based copolymer nylon composite materials of Examples 1 to 4 and Comparative Examples 1 to 6, respectively. The test results are shown in Table 4;
[0141] (1) Glass transition temperature (°C): The glass transition temperature was measured using a DSC test instrument in a nitrogen atmosphere at a heating rate of 10°C / min.
[0142] (2) Transmittance (%): Transmittance test was performed using an ultraviolet spectrophotometer;
[0143] (3) Water vapor transmission rate (cc / m 2 .day.atm): Water vapor transmission rate test is carried out according to standard ASTMF1249-2001;
[0144] (4) Oxygen transmission rate (cc / m 2 .day.atm): oxygen transmission rate test is carried out according to standard GB / T19798-2005;
[0145] (5) Relative viscosity: The relative viscosity of the bio-based copolymer nylon composite material with a concentration of 0.5 g / dL was measured using an Ubbelohde viscometer in a concentrated sulfuric acid solution with a temperature of (25±0.01)°C and a mass fraction of 98%.
[0146] (6) Tensile strength (MPa): Tensile strength test was performed according to ISO 527-1 / -2;
[0147] (7) Flexural strength (MPa): The flexural strength test was performed in accordance with ISO 178.
[0148] Table 4 Test results
[0149]
[0150]
[0151] As shown in Table 4, the bio-based copolymer nylon composite material of the embodiment of the present invention has excellent transparency (light transmittance can reach 91.8%), barrier performance (water vapor transmission rate as low as 15.2cc / m 2 .day.atm and oxygen transmission rate as low as 2.1cc / m 2 .day.atm), heat resistance (glass transition temperature can reach 109°C), mechanical properties (tensile strength can reach 91MPa) and toughness (flexural strength can reach 158MPa). Comparative Example 1 and Comparative Example 1-Comparative Example 2 found that when the bio-based copolymer nylon resin 5T / 510 (PA5T / 510) was used, the prepared bio-based copolymer nylon composite material had excellent transparency and barrier properties. Comparative Example 1 and Comparative Example 3 found that when the nanocellulose contained a carboxyl group, the prepared bio-based copolymer nylon composite material had excellent transparency, barrier properties, heat resistance, mechanical properties and toughness. Comparative Example 1 and Comparative Example 4 found that when the length of the nanocellulose was 200nm, the prepared bio-based copolymer nylon composite material had excellent transparency, barrier properties, heat resistance, mechanical properties and toughness. Comparative Example 1 and Comparative Example 5 show that when the melt extrusion temperature is 265°C, the prepared bio-based copolymer nylon composite material has excellent transparency, barrier properties, heat resistance, mechanical properties and toughness. The inventors analyzed this and believed that the reason may be that when the melt extrusion temperature is high, the melt viscosity of the bio-based copolymer nylon resin can be effectively reduced, thereby improving its fluidity, helping to improve the dispersibility of nanocellulose in the bio-based copolymer nylon resin, so that the nanocellulose and the bio-based copolymer nylon resin undergo more sufficient amide exchange, forming more chemical grafting, and promoting the interface bonding between nanocellulose and the bio-based copolymer nylon resin, so as to better play its reinforcing and modifying role, thereby preparing a bio-based copolymer nylon composite material with excellent transparency, barrier properties, solvent resistance, heat resistance, mechanical properties and toughness; Comparative Example 1, Comparative Example 5 and Comparative Example 6 show that although the bio-based copolymer nylon composite material in Comparative Example 6 has excellent transparency (light transmittance is 91.5%), its barrier property (water vapor permeability is 115cc / m 2 .day.atm and oxygen permeability is 7.6cc / m 2.day.atm), heat resistance (glass transition temperature of 62°C), mechanical properties (tensile strength of 65MPa) and toughness (flexural strength of 86MPa) are all very poor, while the bio-based copolymer nylon composite material prepared in Example 1 of the present invention has excellent transparency (light transmittance can reach 91.8%) and excellent barrier properties (water vapor transmission rate as low as 15.2cc / m 2 .day.atm and oxygen transmission rate as low as 2.1cc / m 2 .day.atm), heat resistance (glass transition temperature can reach 109°C), mechanical properties (tensile strength can reach 91MPa) and toughness (flexural strength can reach 158MPa).
[0152] In summary, the bio-based nylon composite material prepared in the embodiment of the present invention has excellent transparency (light transmittance can reach 91.8%), barrier properties and solvent resistance, and it also has excellent heat resistance (glass transition temperature can reach 109°C), mechanical properties (tensile strength can reach 91MPa) and toughness (bending strength can reach 158MPa), and has broad application prospects in food packaging, medical devices, smart wearable electronics, flexible displays and other fields.
[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A highly transparent and high-barrier bio-based copolymer nylon composite material, characterized in that: The raw materials for preparing the bio-based nylon composite material include bio-based copolymerized nylon resin, nanocellulose, a compatibilizer, an antioxidant and a first auxiliary agent; The bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510 or bio-based copolymer nylon resin 5T / 512.
2. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: In terms of weight, in the preparation raw materials, the bio-based copolymer nylon resin is 92 to 98 parts, the nanocellulose is 1 to 5 parts, the compatibilizer is 1 to 5 parts, the antioxidant is 0.1 to 0.5 parts, and the first auxiliary agent is 0.1 to 2 parts.
3. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: The relative viscosity of the bio-based copolymer nylon resin 5T / 510 is 2.42-2.56, and the relative viscosity of the bio-based copolymer nylon resin 5T / 512 is 2.61-2.
63.
4. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: The length of the nanocellulose is less than 300 nm.
5. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: The carboxyl content in the nanocellulose is 1.2 mmol / g to 3.0 mmol / g.
6. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: The compatibilizer is at least one of ethylene acrylate copolymer, ethylene-octene copolymer grafted with maleic anhydride, and glycidyl methacrylate grafted modified polyether block amide copolymer; And / or, the antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 264, antioxidant TNP, and antioxidant TPP; And / or, the first auxiliary agent includes a lubricant.
7. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 1, characterized in that: The preparation process of the bio-based copolymer nylon resin is as follows: The dibasic acid, terephthalic acid and deionized water are mixed, and then 1,5-pentanediamine is added to carry out a neutralization reaction to obtain a mixed solution of nylon 5T salt; The catalyst, the end-capping agent, the second auxiliary agent and the mixed solution of the nylon 5T salt are mixed and concentrated and prepolymerized to obtain a nylon 5T prepolymer; The nylon 5T prepolymer is polymerized under vacuum negative pressure conditions to obtain a bio-based copolymer nylon resin.
8. The highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 7, characterized in that: The dibasic acid is sebacic acid or dodecanedioic acid; When the dibasic acid is sebacic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 510; When the dibasic acid is dodecanedioic acid, the prepared bio-based copolymer nylon resin is bio-based copolymer nylon resin 5T / 512.
9. A method for preparing the highly transparent and high-barrier bio-based copolymer nylon composite material according to any one of claims 1 to 8, characterized in that: include: Preparation of bio-based copolymer nylon resin; Preparation of bio-based copolymer nylon composites: The bio-based copolymer nylon resin, nanocellulose, compatibilizer, antioxidant and first auxiliary agent are mixed and dispersed to obtain a mixture, and then the mixture is melt-extruded, pulled and granulated in a screw extruder to obtain a bio-based copolymer nylon composite material.
10. The method for preparing the highly transparent and high-barrier bio-based copolymer nylon composite material according to claim 9, characterized in that: The temperature of the melt extrusion is 260°C to 280°C.
Citation Information
Patent Citations
Preparation method of high barrier property polyethylene / nylon 6 in-situ nanocomposite material
CN101768302A
Biomass nanocrystal enhanced type nylon composite material, composite master batch and preparation method
CN104497561A
Natural fiber reinforced bio-based nylon material and preparation method thereof
CN110452530A
Preparation method of intrinsic flame-retardant high-temperature-resistant nylon composite material as well as product and application thereof
CN117866431A
Resin composition and molding
JP2023062297A
Cited By
Bio-based polyamide elastomer fiber as well as preparation method and application thereof
CN120797244A